Giant submandibular sialolipoma masquerading as huge goitre: a case report - Sentilnathan Subramaniam; Syamim Johan; Firdaus Hayati; Ng, Chiak Yot; Nornazirah Azizan; Jitt Aun Chuah; Irfan Mohamad (2020)
Background: Sialolipoma is a rare tumour which may arise from both major and minor salivary glands and has recently been described as a variant of salivary gland lipomatous lesions. Case presentation: We report a 54-year-old male who presented with a 7-year history of large right anterior neck swelling. He was clinically euthyroid and had no compressive or infiltrative symptoms. He sought medical attention due to the discomfort exerted by the weight of the mass and was keen for excision. The swelling appeared like a goitre but physical examination proved otherwise. Imaging was suggestive of a benign tumour arising from the right parapharyngeal fossa. The mass was surgically excised and was noted to be adherent to part of the submandibular gland. Histopathological examination revealed a new variant of benign adipocytic tumour of salivary gland or sialolipoma arising from the submandibular gland. Besides being the largest sialolipoma to be reported, there are also no reports of giant submandibular sialolipomas masquerading as a huge goitre in appearance. Conclusion: Submandibular sialolipomas can present in really large sizes and appear as a giant goitre. It is important to differentiate between benign lipomas from liposarcomas and tailor the management accordingly. Surgical enucleation is the preferred choice of treatment for these benign tumours with low recurrence rates.